Using Wearable Devices to Examine the Associations of Sedentary Behavior with Perceived and Performance Fatigability Among Older Adults: The Study of Muscle, Mobility and Aging (SOMMA) - Reagan E. Garcia; Anne B. Newman; Eileen Johnson; Yujia Susanna Qiao; Peggy M. Cawthon; Barbara J. Nicklas; Bret H. Goodpaster; Nancy W. Glynn (Sensors)
Fatigability, a phenotype of poor energy regulation, is associated with lower physical activity in older adults, but independent associations with sedentary behavior are unknown. We examined whether sedentary behavior was associated with fatigability using cross-sectional data from the Study of Muscle, Mobility and Aging. Mean sedentary time, sedentary bout length, and sedentary breaks/day were measured using 7-day waking hour data collected from a thigh-worn accelerometer. Fatigability was assessed using the Pittsburgh Fatigability Scale Physical subscale (PFS, score 0–50, higher = greater fatigability) and the Pittsburgh Performance Fatigability Index (PPFI), a percentage decline of observed cadence to maximal cadence from a wrist-worn accelerometer captured during a usual-paced 400 m walk (range 0–100%, higher = more performance deterioration). The participants (N = 663; 76.4 ± 5.1 years, 58% women, 54% high PFS, median PPFI 1.4%) were sedentary for 614.8 ± 111.7 min/day, with a mean 15.0 ± 5.5 min/day bout length and mean 46.1 ± 13.2 sedentary breaks/day. Higher total sedentary time was associated with greater PFS Physical score (β = 0.71, p = 0.0368), but this association was not independent of step count/day. After adjusting for step count/day, higher sedentary time was associated with lower PPFI score (β = −0.44, p = 0.0039). Sedentary bout length and breaks/day were not associated with perceived or performance fatigability. Future studies should aim to better understand the inter-relatedness of these behaviors.